Interest of Supportive and Barrier Protective Skin Care Products in the Daily Prevention and Treatment of Cutaneous Toxicity During Radiotherapy for Breast Cancer. (23rd January 2018) - Berger, Antoine; Regueiro, Carlos; Hijal, Tarek; Pasquier, David; De La Fuente, Cristina; Le Tinier, Florence; Coche-Dequeant, Bernard; Lartigau, Eric; Moyal, Dominique; Seité, Sophie; Bensadoun, René-Jean
Purpose: As many as 50% of patients with cancer develop acute skin reactions to some degree with radiotherapy. Proactive skin care is often recommended to minimise these skin reactions and maintain the integrity of the epidermal barrier; nevertheless, no consensual guidelines are systematically used. This multicentre, observational, prospective study evaluated the tolerability and benefit of supportive and barrier protective skin care products in preventing radiotherapy-induced skin reactions in 253 women initiating radiotherapy (exclusive or adjuvant) for breast cancer. Methods: Patients received a kit of 5 commercially available skin care products before the first radiotherapy treatment. The following variables were assessed: cutaneous adverse events, investigator-assessed skin reactions (oedema, erythema, dryness, desquamation) before and after radiotherapy course, investigator, and patient opinion on products benefit. Results were analysed by frequency of product use (heavy versus low). Results: Average age was 60 years (range: 34-85). Over 92% of patients reported good to excellent tolerance on irradiated skin for each product. During the 6-week radiotherapy period, we observed that heavy product users had less skin reactions than the low users, particularly within 10 days of radiotherapy initiation (8% versus 18%; p = .031). Positive physician's opinion on product use was more frequent for high (66.6%) versus low (32%) users. Patient-assessed patient benefit index was generally >1, indicating relevant treatment benefit, with a tendency for better benefit in high versus low users. Conclusions: These results support recommendations to use skin care products to minimise the impact of secondary cutaneous reactions with radiotherapy cancer treatment.